Effects of Gruel Feeding and Oral Dextrose on the Survivability of Pigs After Weaning - Madie R. Wensley; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M. DeRouchey; Ty H. Kim; Andy W. Boschert; Ethan E. Stephenson; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
Two experiments were conducted using 3,087 (Exp. 1) and 988 (Exp. 2) pigs to determine the effect of gruel feeding (Exp. 1) and administering oral dextrose (Exp. 2) on pig survivability after weaning. Upon arrival to the nursery, the smallest 10% of pigs were selected and randomly placed in designated pens with 61 to 108 pigs per pen. Pens of small pigs were assigned to 1 of 2 treatments in a completely randomized design. Treatments consisted of gruel feeding two or four times per day starting 14-d post-placement. At each gruel feeding, approximately 2.5 lb of solid feed was added to a round Rotecna bowl (Rotecna S.A., Agramunt, Spain) located at the front of the pen. Water was added to feed at a decreasing rate over time such that d 0 to 5, 6 to 10, and 11 to 14 the ratio of water to feed was 3:1, 1:1, and 1:3, respectively. In Exp. 2, every other pig removed from general population or pens of small pigs for welfare considerations (lameness, sick, or fallback) received a single 10 mL oral dose of a 50% dextrose solution (Vet One, MWI Animal Health, Boise, ID), as a source of glucose, before being placed in a removal pen. All removed pigs were tagged and weighed, blood glucose measured prior to and 30 min after entering removal pens, and their body temperature recorded. Overall, gruel feeding the small pigs two or four times per day for 14-d post-placement did not influence (P>0.10) mortality from weaning to the end of gruel feeding (3.78 vs. 4.25%, respectively). Likewise, dextrose administration did not influence (P>0.10) pig mortality after removal to approximately d 38 after weaning (21.4 vs. 23.4% respectively), even though blood glucose levels increased (P<0.001) for pigs administered dextrose compared to pigs not administered dextrose (increased by 11.4 vs. 19.1 mg/dL). An interaction was observed for blood glucose and body temperature (P<0.001). Pigs with a blood glucose less than 70 mg/dL had increased mortality as body temperature at removal increased. In contrast, pigs with a blood glucose between 70 and 120 mg/dL or greater than 120 mg/dL had decreased mortality as body temperature increased. Pigs weighing less than 10 lb at removal had an increased mortality (P<0.001) compared to pigs weighing greater than 10 lb at removal. In summary, gruel feeding four times per day vs. two times per day or providing removed pigs glucose supplementation did not improve survivability of pigs after weaning. Additionally, removed pigs with low body weight, body temperature below or above the normal range, or high blood glucose had decreased survivability.
Keywords: dextrose; glucose supplement; gruel feeding; mortality; nursery pig; weaning